The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/ac070433l
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of C-Reactive Protein on Amide-Linked N-Hydroxysuccinimide−Dextran Arrays with a Spectral Surface Plasmon Resonance Biosensor for Serodiagnosis

Abstract: A new label-free array system using amide-linked (AL) NHS-dextran and a spectral SPR biosensor are presented for the high-throughput analysis of C-reactive protein (CRP) in human sera. The AL NHS-dextran layer on the surface of gold arrays was composed of an amide linkage between NHS-modified carboxymethyl-dextran and amine-modified 11-mercaptoundecanoic acid. The topology of the AL NHS-dextran layer was analyzed by atomic force microscopy, and it was found to be superior to the previously used epoxide-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…After AFM studies, they found this surface [47] more suitable for proteins immobilization than a normal epoxide-linked carboxymethyl-dextran layer. Monoclonal anti-CRP antibodies were immobilized onto the surface and rapid analysis of CRP was performed down to 20 μg/L (∼0.8 nM) concentration in 120 human sera diluted (1:10 in PBS, pH 7.4); results showed a good correlation with the turbidimetry reference immunoassay [55].…”
Section: Protein Biomarkers For Multiple Diseasesmentioning
confidence: 99%
“…After AFM studies, they found this surface [47] more suitable for proteins immobilization than a normal epoxide-linked carboxymethyl-dextran layer. Monoclonal anti-CRP antibodies were immobilized onto the surface and rapid analysis of CRP was performed down to 20 μg/L (∼0.8 nM) concentration in 120 human sera diluted (1:10 in PBS, pH 7.4); results showed a good correlation with the turbidimetry reference immunoassay [55].…”
Section: Protein Biomarkers For Multiple Diseasesmentioning
confidence: 99%
“…However, the equipment required can be bulky and expensive, but emerging technologies will lead to significant reductions in size. SPR assays have found many applications in different fields such as biomedical diagnostics [88,89], and drug discovery [90,91]. …”
Section: Direct Optical Detectionmentioning
confidence: 99%
“…Within biosensor technology surface plasmon resonance (SPR) is considered to be a real-time and label-free tool [2]. Over the past two decades SPR has found its way into medical diagnostics [35], environmental analysis [69] and food control [912]. The working principle is based on changes in the refractive index at interfaces.…”
Section: Introductionmentioning
confidence: 99%